Radiocapitellar plica syndrome: non-operative treatment in an adolescent artistic gymnast - Frank, S. M.; Gubanich, P. J. (Journal of Athletic Training, 2019)
Background: The formation of synovial plicae, especially in the knee, has been well described in the literature. Less commonly, the plica can become inflamed and painful (knee plica syndrome) with a reported prevalence of 2.1% in adolescent female athletes. Plica syndrome can also occur at the elbow but is rare and easily misdiagnosed due to symptoms that mimic other common elbow injuries. There is no true consensus regarding the diagnosis and treatment of this pathology, but findings indicate that operative care outperforms conservative care. Evidence regarding best practice for elbow plica syndrome is extremely sparse in adolescent overhead athletes and absent in gymnasts. We present a Level 3 CASE Study on radiocapitellar plica syndrome. Patient: A 16-year-old female gymnast presented to the sports medicine clinic with a three-week history of left posterior elbow pain. The patient reported no specific trauma, however her upper extremity biomechanics were recently altered due to a right wrist injury. Her main complaints were sharp pain, repetitive clicking, and an inability to fully extend the elbow. Upon examination, she presented with painful terminal elbow extension and initial radiographs were normal. MRI was obtained and revealed a prominent posterolateral synovial plica measuring up to 6 mm in length and 2 mm in thickness posteriorly. The patient was diagnosed with radiocapitellar plica syndrome. Intervention or Treatment: Rest from gymnastics and formal physical therapy were initiated. The family was referred to an orthopaedic surgeon if conservative care failed. Symptoms persisted for approximately four weeks, but upon initiation of an iontophoresis treatment regimen (1.5mL dexamethasone) twice-per-week, symptoms improved. After one month of iontophoresis and traditional rehabilitation, the patient reported being symptom-free. She made a full return to gymnastics approximately 11-weeks from initial visit. No reoccurrence of symptoms has been reported. Outcomes or Other Comparisons: The clinical findings of our patient were similar to other reported cases in the literature: pain over the radiocapitellar joint line, sharp pain with terminal extension, end range extension deficit, and painful snapping or locking. However, our patient's symptoms resolved with conservative care which contradicts research suggesting surgical resection is the preferred treatment, producing excellent outcomes of greater than 90%. Additionally, previous known cases of elbow plica syndrome in adolescents were resolved with surgical resection. To our knowledge, only one study examined overhead athletes (throwers and golfers) and none included gymnasts. Conclusions: We present a case of radiocapitellar plica syndrome in an adolescent gymnast with full resolution of symptoms via conservative care. While plica syndrome is a known entity, the combination of our patient's age (16), affected joint (elbow), chosen sport (artistic gymnastics), and treatment plan (non-operative) is unique among the reported literature. Although uncommon, plica syndrome should be part of a complete differential diagnosis when faced with posterior elbow pain, clicking/snapping sensations, and pain upon full extension, especially in athletes who perform repetitive overhead tasks. Athletic trainers are in a unique position to recognize symptoms of elbow plica and make appropriate referrals. Health care professionals should be wary to label elbow pain as standard tendinitis; advanced evaluation may be necessary to diagnose the true source of pain. Lastly, though the literature demonstrates successful treatment of symptomatic plica syndrome by surgical resection, this case suggests that a period of conservative care is warranted, especially in the adolescent population. Clinical Bottom Line: Plica syndrome should be considered as part of a thorough examination of new elbow pain. Despite indications that surgical intervention is more successful, this case offers fresh evidence to support the non-operative approach. Further research on radiocapitellar plica syndrome is needed in adolescent overhead athletes to determine best practice in this unique demographic.